KESIAPAN LABORATORIUM BIOLOGI DALAM MENUNJANG KEGIATAN PRAKTIKUM SMA NEGERI DI KABUPATEN BREBES - Indriastuti, Indriastuti; Herlina, Lina; Widiyaningrum, Priyantini (Journal of Biology Education, 2013)
The purpose of researcs was to know a readiness of the biology laboratory at High Schools in Brebes Regency in supporting a practical activity. The method that is used is descriptive qualitative. The object of this research are students of Senior High Schools in Brebes Regency. Sampling technique in the research has been done by stratified random sample technique based ofÂ  school achivments status that is RSBI (InternationalÂ  Path of School Standard), SKM (SelfSchool Category) and GeneralStateSchool Category. This research has been done at Biology Laboratories ofÂ  SMAN 1 Bulakamba and SMAN 1 Losari as General State School Category, SMAN 1 Tanjung dan SMAN 3 Brebes as InternationalÂ  Path of School Standard (RSBI). Data in the form of qualitative data. Variables were measured included three indicators of facilities, infrastructure and laboratory activities readiness.Â  The result of the research showed that level of readiness in providing facilities and infrastructure, management readiness of practice implemention and readiness of laboraty activities processing gradually scores for 67,40%, 83,75% and 68,72%. This researchâs conclusion is biology laboratories of Senior High Schools in Brebes regency belong to ready category in supporting a practical activity with preparation range is 73,29%.Â Â Penelitian ini bertujuan untuk mengetahui tingkat kesiapan laboratorium biologi SMA Negeri di Kabupaten Brebes dalam menunjang kegiatan praktikum. Metode yang digunakan deskriptif kualitatif, populasi penelitianadalah seluruh SMA Negeri di Kabupaten Brebes. Pengambilan sampel penelitiandilakukan dengan teknik stratified random sample berdasarkan status prestasi sekolah, yaitu RSBI (Rintisan Sekolah Bertaraf Internasional), SKM (Sekolah Kategori Mandiri) dan Sekolah Negeri kategori biasa. Penelitian ini dilakukan pada laboratorium biologi SMAN 1 Bulakamba dan SMAN 1 Losari sebagai sekolah negeri kategori biasa, SMAN 1 Tanjung dan SMAN 3 Brebes sebagai sekolah negeri kategori mandiri dan SMAN 2 Brebes sebagai sekolah rintisan bertaraf internasional.Variabel yang diukur meliputi tiga indikator kesiapan, yakni kesiapan sarana dan prasarana, kesiapan pengelolaan penyelenggaraan praktikum dan kesiapan kegiatan laboratorium. Hasil penelitian menunjukkan, bahwa tingkat kesiapan laboratorium dalam menyediakan sarana dan prasarana, kesiapan pengelolaan penyelenggaraan praktikum dan kesiapan kegiatan laboratorium secara berturut-turut memperoleh skor 67,40%, 83,75% dan 68,72%. Simpulan penelitian ini adalah, laboratorium biologi SMA Negeri di Kabupaten Brebes siap dalam menunjang kegiatan praktikum pada pembelajaran biologi dengan rata-rata tingkat kesiapan sebesar 73,29%.